2021
DOI: 10.1155/2021/9539765
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Imaging Technology of Anterior Segment of the Eye

Abstract: Advances in imaging technology and computer science have allowed the development of newer assessment of the anterior segment, including Corvis ST, Brillouin microscopy, ultrahigh-resolution optical coherence tomography, and artificial intelligence. They enable accurate and precise assessment of structural and biomechanical alterations associated with anterior segment disorders. This review will focus on these 4 new techniques, and a brief overview of these modalities will be introduced. The authors will also d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 96 publications
0
6
0
Order By: Relevance
“…Kenia et al ( Kenia et al, 2020 ) found similar correlations between DAR, IR and SE. Vinciguerra screening parameters are a series of newly developed parameters based on an attempt to differentiate normal corneas from keratoconus corneas ( Han et al, 2021 ). Smaller DAR and IR values indicated a softer cornea ( Han et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kenia et al ( Kenia et al, 2020 ) found similar correlations between DAR, IR and SE. Vinciguerra screening parameters are a series of newly developed parameters based on an attempt to differentiate normal corneas from keratoconus corneas ( Han et al, 2021 ). Smaller DAR and IR values indicated a softer cornea ( Han et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Vinciguerra screening parameters are a series of newly developed parameters based on an attempt to differentiate normal corneas from keratoconus corneas ( Han et al, 2021 ). Smaller DAR and IR values indicated a softer cornea ( Han et al, 2021 ). However, CCT and bIOP had a greater impact on most corneal deformation parameters ( Table 2 ), which was similar to previous studies ( Sedaghat et al, 2020 ; Yu et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Advances in ML technology, particularly DL algorithms, have enabled the application of AI in various anterior segment diseases, including DED. AI is expected to be able to integrate the data from medical records, test results, and large population-based studies and provide optimized protocols for the diagnosis and management of DED [ 15 ]. The analysis of data obtained by imaging devices for DED, such as ASP, meibography, tear interferometry, IVCM, and AS-OCT, using AI may enable the precise and accurate assessment of the tests for DED, which would be critical for proper diagnosis and optimal treatment of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…This diagnostic algorithm showed high sensitivity (86.4%) and specificity (91.7%), suggesting that the integration of OCT corneal epithelial mapping data into a diagnostic algorithm using AI may improve the reliability of the diagnosis of DED [ 117 ]. Although a limited number of studies regarding the application of AI for the analysis of AS-OCT images have been conducted so far, the development of advanced devices, including high-resolution OCT, may enable the assessment of subtle changes in the ocular surface and tear film using AI [ 15 ].…”
Section: Application Of Ai In Diagnosis and Treatment Of Dedmentioning
confidence: 99%
See 1 more Smart Citation